Asthma medication is increasingly prescribed for Finnish Olympic athletes - For a reason? - Aavikko, A.; Helenius, I.; Alaranta, A.; Vasankari, T.; Haahtela, T. (Journal of Asthma, 2012)
Use of asthma medication is common among athletes. In 2009, the World Anti-Doping Committee (WADA) and the International Olympic Committee removed the need to document asthma by lung function tests before the use of inhaled ß2-agonists. Methods: We assessed the changes in asthma medication use in Finnish Olympic athletes 8 years apart in 2002 (N = 446) and 2009 (N = 372). The athletes filled out a questionnaire on asthma symptoms, diagnosis, and medication. Results: The use of asthma medication increased from 9.4% in 2002 to 12.6% in 2009 (adjusted odds ratio (OR) = 1.71, 95% confidence interval (CI) 1.08-2.69). Fixed combinations of inhaled long-acting ß2-agonists (LABAs) and inhaled corticosteroids (ICSs) were used three times more in 2009 vs. 2002 (OR = 3.38, 95% CI 1.26-9.12). At the same time, no significant changes were observed in the occurrences of physician-diagnosed asthma (13.9% vs. 15.9%) or wheezing (10.3% vs. 10.2%). In 2002, all athletes on asthma medication also had a physician-diagnosed disease, but in 2009, 11.8% of the athletes on medication were lacking it. Conclusions: Especially, the use of combination therapy of LABAs and ICSs is increasing among Finnish Olympic athletes. This trend is worrying as it is not based on increasing occurrence of symptoms, asthma diagnoses, or objective lung function measurements. More data, also from other countries, are needed to change recommendations or WADA rules.